Municipal Deposits in Ukraine during 2016-2018: Opportunities and Threats for Financial System - Anna, Anna; Kornyliuk, Roman; Ivasiv, Ihor; Zaborovets, Yuliya (International Journal of Engineering and Technology, 2018)
In the article the local authorities’ temporarily free funds allocation policy in terms of banks, interest rates and regions was explored. The results of the research show that the largest amounts of deposits are concentrated in Donetsk and Dnipropetrovsk regions. The leader in deposit attraction is Ukrgasbank, despite the fact that it is just fourth in terms of net assets among state-owned banks. It can be stated that municipal deposits became an important source of liquidity for Ukrainian banking system. On the other hand some systemic threats for financial instability are related to the rapid growth of municipal deposits volumes due to decentralisation.  Regulatory requirement for allocation of such deposits in state-owned banks reduces possibilities for fair banking competition. Also operational ineffectiveness of state-owned banks results in huge interest costs which are finally compensated by government capital injections from the state budget.